Assessment of fungal bioagents against Tilletia indica causing Karnal bunt of wheat (Triticum aestivum) - SMITA, SANGALE; GURJAR, MALKHAN SINGH; MAHENDRA, MUTHYALA; KASHYAP, NATASHA; KUMAR, JITENDRA; NEBAPURE, SURESH M; BAG, TUSHAR KANTI; RANA, VIRENDRA SINGH; SAHARAN, MAHENDER SINGH (The Indian Journal of Agricultural Sciences, 2025)
Wheat (Triticum aestivum L.) is an important cereal crop grown worldwide. Among biotic, Tilletia indica is a quarantine pathogen, causing Karnal bunt of wheat and it has a zero-tolerance limit. The present experiment was conducted during 2023 and 2024 at ICAR-Indian Agricultural Research Institute, New Delhi to assess the efficacy of few fungal biocontrol agents against T. indica. Up on in vitro and in planta conditions, 18 Trichoderma asperellum and 15 Trichoderma harzianum isolates were assessed against T. indica. Using the well diffusion assay with crude extract of Trichoderma spp., the highest percent inhibition was shown by T. asperellum 6413 (T17) with 42.07% and 63.97% inhibition of Ti12 and Ti18 isolates of T. indica, respectively followed by T. asperellum 8619 (T2) with 37.93% inhibition of Ti12 and 61.07% inhibition of Ti18 isolates of T. indica under in vitro analysis. T. harzianum isolates were not found effective. The GC-MS analysis revealed the presence of several volatile organic compounds (VOCs) were in T. asperellum 6413 (T17) and T. asperellum 8619 (T2). However, volatile organic compounds, viz. heptanes, 2, 3-Butanediol, and 1-Hexanol, having antifungal properties were common in both the T. asperellum 6413 and T. asperellum 8619 and 2 H-Pyran-2-one, acetic acid and toluene were exclusively present in T. asperellum 8619. In addition, in planta studies with two fungal biocontrol agents revealed that pre-and post-inoculation application of asperellum 6413 (29.49% and 30.75%) showed the significant inhibition of Karnal bunt pathogen.